Large erupted complex odontoma - Vijeev Vasudevan; V Manjunath; Radhika Manoj Bavle (Wolters Kluwer Medknow Publications, 2009)
Odontomas are a heterogeneous group of jaw bone lesions, classified as odontogenic tumors which usually include well-diversified dental tissues. Odontoma is a term introduced to the literature by Broca in 1867. Trauma, infection and hereditary factors are the possible causes of forming this kind of lesions. Among odontogenic tumors, they constitute about 2/3 of cases. These lesions usually develop slowly and asymptomatically, and in most cases they do not cross the bone borders. Two types of odontoma are recognized: compound and complex. Complex odontomas are less common than the compound variety in the ratio 1:2.3. Eruption of an odontoma in the oral cavity is rare. We present a case of complex odontoma, in which apparent eruption has occurred in the area of the right maxillary second molar region.